2003
DOI: 10.1002/lsm.10114
|View full text |Cite
|
Sign up to set email alerts
|

Novel model for evaluation of epidermal preservation and dermal collagen remodeling following photorejuvenation of human skin

Abstract: Background and Objectives: In order to optimize photorejuvenation of human skin, a method must be developed to reliably compare the potential for epidermal preservation and dermal fibroblast stimulation of different laser devices and irradiation parameters. We describe a novel human skin tissue culture model developed for this purpose. Materials and Methods: An artificial skin model, consisting of human keratinocytes in the epidermis and human fibroblasts and rat-tail collagen in the dermis, was cultured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…As we noted significant epidermal damage for continuous spurts longer than 80 millisecond, 1.85 seconds appears to be the maximum permissible time that the skin surface can be exposed to sub-zero temperatures without inducing cryo-injury. As described in the Introduction, we have previously demonstrated the usefulness of the RAFT model for evaluating wound healing response after irradiation with photorejuvenation devices [11]. This paper identifies an additional indication for this tissue culture model, evaluation of cryogen-induced effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we noted significant epidermal damage for continuous spurts longer than 80 millisecond, 1.85 seconds appears to be the maximum permissible time that the skin surface can be exposed to sub-zero temperatures without inducing cryo-injury. As described in the Introduction, we have previously demonstrated the usefulness of the RAFT model for evaluating wound healing response after irradiation with photorejuvenation devices [11]. This paper identifies an additional indication for this tissue culture model, evaluation of cryogen-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the usefulness of an in vitro model of human skin (floating collagen gel: RAFT) to evaluate the wound healing response after irradiation with devices used for photorejuvenation [11]. The RAFT model mimics in vivo human skin in terms of structure, cellular activity, and function [12].…”
Section: Introductionmentioning
confidence: 99%
“…In comparable studies, human subjects have been used; however, using humans provides two intrinsic difficulties: ͑1͒ in measuring gene expression on a single subject over time and ͑2͒ in stringent medical limits ͑ethical and practical͒ of harvesting tissue samples at multiple times for histological and biochemical analysis. 15,16 In light of these difficulties, animal models are used as a more viable model to study hsp70 expression and other laser-induced tissue effects. 5,17 The porcine model is the closest nonprimate equivalent to human skin and is the most widely used dermal wound repair model, but because of differences in tissue architecture and immune responses, even it does not accurately reflect human wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the RAFT organotypic culture model 4,[9][10][11] has been developed to study wound healing. A RAFT is an artificial tissue model consisting of fibroblasts embedded in a collagen gel with or without keratinocytes seeded on the surface.…”
Section: Original Articlementioning
confidence: 99%
“…The RAFT cultures with keratinocytes resemble skin and simulate the extracellular matrix and native environment of fibroblasts. 9 This provides a more natural growth environment in which to investigate fibroblast activity. Figure 1 depicts the layers, cellular components, and extracellular matrix of a RAFT tissue construct.…”
Section: Original Articlementioning
confidence: 99%